The Potential of Bacillus subtilis and Pseudomonas aeruginosa in Reducing Hg²⁺ Levels in Small-Scale Gold Mining Liquid Waste in Indonesia - Sekarsari Wibowo; Abiyyu Armijn Firman Firdaus; Abdillah Akmal Karami (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Mercury contamination resulting from artisanal and small-scale gold mining (ASGM) poses a significant threat to both environmental and human health. This study evaluates the effectiveness of two bacterial strains, Bacillus subtilis and Pseudomonas aeruginosa, in reducing mercury (Hg²⁺) concentrations in ASGM liquid waste. Methods: Experiments were conducted over seven days under controlled conditions, with two pH settings (neutral and alkaline), by monitoring total mercury reduction and bacterial growth (CFU/mL). Result and discussion: Results indicated that B. subtilis achieved the highest mercury removal efficiency—up to 90.07% at neutral pH and 89.51% at alkaline pH. P. aeruginosa also showed high efficacy, though slightly lower in comparison. Colony counts peaked on day two but declined by day seven, likely due to nutrient depletion and mercury toxicity, particularly at neutral pH. In contrast, control reactors without bacterial inoculation showed negligible changes in Hg concentration and no significant colony development. Conclusion: Despite the decline in bacterial counts over time, both strains remained functionally active, demonstrating strong adaptability and potential as effective bioremediation agents for mercury-contaminated wastewater. These findings support the integration of bacterial bioremediation as a viable component of sustainable mercury management in ASGM sectors.